Two-Dimensional Model for Pore Pressure Accumulations in the Vicinity of a Buried Pipeline - Zhao, Hongyi; Jeng, Dong-Sheng; Guo, Z.; Zhang, J. (Journal of Offshore Mechanics and Arctic Engineering, 2014)
In this paper, we presented an integrated numerical model for the wave-induced residual liquefaction around a buried offshore pipeline. In the present model, unlike previous investigations, two new features were added in the present model: (i) new definition of the source term for the residual pore pressure generations was proposed and extended from 1D to 2D; (ii) preconsolidation due to self-weight of the pipeline was considered. The present model was validated by comparing with the previous experimental data for the cases without a pipeline and with a buried pipeline. Based on the numerical model, first, we examined the effects of seabed, wave and pipeline characteristics on the pore pressure accumulations and residual liquefaction. The numerical results indicated a pipe with a deeper buried depth within the seabed with larger consolidation coefficient and relative density can reduce the risk of liquefaction around a pipeline. Second, we investigated the effects of a trench layer on the wave-induced seabed response. It is found that the geometry of the trench layer (thickness and width), as well as the backfill materials (permeability K and relative density Dr) have significant effect on the development of liquefaction zone around the buried pipeline. Furthermore, under certain conditions, partially backfill the trench layer up to one pipeline diameter is sufficient to protect the pipelines from the wave-induced liquefaction. Griffith Sciences, Griffith School of Engineering No Full Text